2015
DOI: 10.1155/2015/513435
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Supply Chain Cooperative Inventory Model with Payment Period Being Dependent on Purchasing Price under Defective Rate Condition

Abstract: In most commercial transactions, the buyer and vendor may usually agree to postpone payment deadline. During such delayed period, the buyer is entitled to keep the products without having to pay the sale price. However, the vendor usually hopes to receive full payment as soon as possible, especially when the transaction involves valuable items; yet, the buyer would offer a higher purchasing price in exchange of a longer postponement. Therefore, we assumed such permissible delayed period is dependent on the pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…A high defect rate influences negatively production costs as well as might perhaps result in a process shortage. Moreover, it might increase the storage rate in manufacturing (Yang et al, 2015). All waste sources must be identified and eliminated because defectives are a form of production waste (Ohno, 1988).…”
Section: Defective Ratementioning
confidence: 99%
“…A high defect rate influences negatively production costs as well as might perhaps result in a process shortage. Moreover, it might increase the storage rate in manufacturing (Yang et al, 2015). All waste sources must be identified and eliminated because defectives are a form of production waste (Ohno, 1988).…”
Section: Defective Ratementioning
confidence: 99%
“…Under order-quantity-dependent trade credit, Yueli et al [10] assumed the newsvendor model with stochastic demand and shortage and concluded that higher delay periods would increase the profit. When a three-echelon supply chain is assumed, Yang et al [11] obtained the maximum joint profit of a two-level trade credit for a single product with defective production and repair rate. In order to obtain the optimal fuzzy total cost, Shabani et al [12] established a two-warehouse mathematical inventory model under trade credit contract.…”
Section: Introductionmentioning
confidence: 99%